Is youth's engagement in agribusiness an opportunity or a necessity? A closer look at the situation in South Kivu, Eastern Democratic Republic of the Congo - Mangole, C.D.; Dontsop-Nguezet, P.; Feleke, S.; Manyong, V.; Christian, K.K.; Bamba, Z.; Abdoulaye, T. (2025)
Despite the broad focus on necessity- and opportunity-driven entrepreneurship in research and policy, the entrepreneurial dichotomy within the agribusiness context has not been adequately addressed. This study contributes to closing this knowledge gap by examining youth's perceptions of agribusiness through the lens of the push-pull motivation framework. Results reveal that 47% of youth are driven into agribusiness by both necessity and opportunity, while 41% by necessity alone and only 12% by opportunity alone. Key factors shaping youth's perceptions include gender, education, food processing participation, agribusiness-related training, land ownership, monthly income, and family farming background. The result further identifies significant heterogeneity in the drivers of perceptions—based on location, gender, and agribusiness roles, suggesting the need to tailor agricultural program interventions to ensure the best fit. Notably, enhancing access to formal education and agribusiness training, encouraging participation in food processing, and improving land access are critical to enhancing youth participation in agribusiness.